The translation of English it-cleft sentences into Indonesian - Suastini, Ni Wayan (International journal of linguistics, literature and culture, 2016)
The translations of English It-Cleft Sentences into Indonesian is the topic of this study. It is interesting to study because there is cleft construction in Indonesian. Since there is no cleft construction in Indonesian, sometimes the result of the translation can be awkward. The purposes of this study are to find out the translation of English cleft sentences into Indonesian found in The Intelligent Investor book and to analyze the naturalness of the translation in Indonesian. The sentences were collected through note taking technique and then analyzed qualitatively by using the theories of Quirk (1986) regarding cleft sentences, and Newmark (1988) related to the levels of translation. The results show that the sentences were translated into both simple and complex sentences in the Indonesian TL. From the translation results can be seen that not all of the sentences sound natural in the target language because the cleft construction is not found in Indonesian, however, the meaning of the sentence can be transferred into the target language.